A novel PV based high voltage gain soft switching DC-DC boost converter - Jagadeesh, Ingilala; Indragandhi, V (International Journal of Engineering and Technology, 2018)
The design of high voltage gain DC-DC boost converter is carried out with the addition of the Voltage Multiplier (VM) method. Here the coupled inductor and VM methodologies are proposed to reduce the switching and conduction losses of the Metal Oxide Semiconductor Field Effect Transistor (MOSFET). The Zero Current Switching (ZCS) technique with coupled inductor leakage inductance is used to operate the MOSFET. The leakage inductance is used to decrease the reverse recovery current across the diode. The design procedure of the boost converter and corresponding output waveforms are presented in this paper. Photovoltaic (PV) source converter with coupling inductors soft switching technique has been analyzed and tested in this paper.Â Â